Legislation’s Disharmony in Addressing Child Exploitation - Jannah, Rauzatul; Mohd. Din; Muhammad Insa Ansari (International Journal of Sociology and Law, 2026)
Child exploitation is a multifaceted socioeconomic problem and continues to be a significant difficulty in Indonesia. The prevention of child exploitation is normatively governed by several legislative instruments, including Law Number 35 of 2014 on Child Protection, Law Number 13 of 2003 on Manpower, Law Number 21 of 2007 on the Eradication of Trafficking in Persons, Law Number 12 of 2022 on Sexual Violence Crimes, Aceh Qanun Number 11 of 2008 on Child Protection, and Aceh Qanun Number 7 of 2014 on Manpower. The multiplicity of this legislation has resulted in legal issues characterised by norm disharmony, so undermining the efficacy of child protection. This research aims to examine the disagreement among rules concerning child exploitation. The employed research method is normative legal research, utilising a legislative approach. The utilised data sources comprise secondary data, including primary, secondary, and tertiary legal materials, gathered through literature review and analysed qualitatively in a descriptive manner. The research findings indicate a lack of coherence in legislation both horizontally and vertically, encompassing inconsistencies in the definition of child exploitation, variations in the minimum age for child employment, discrepancies in criminal penalties, misalignment in the regulation of sexual exploitation, and divergences between national laws and the Aceh Qanun.